107 The relationship between shoulder pain, physical exam findings, and structural pathology in elite wheelchair athletes. (3rd March 2020) - Blauwet, Cheri; Derman, Wayne; Webborn, Nick; Morrissey, Dylan; Chakraverty, Julian; Martin, Paul; Idrisova, Guzel
Abstract : Background: Although athletes who are wheelchair users for both daily activity and sport participation are at high risk for shoulder injuries, little is known regarding the characteristics of shoulder injury in this population. Objective: To determine the relationship between shoulder symptoms (SS), physical exam findings (PEF), and structural pathology (SP) in elite wheelchair athletes competing in athletics and powerlifting Design: Cross-sectional study. Setting: Three international competitions. Participants: 80 elite wheelchair athletes competing in track (n=40), field (n=19) and powerlifting (n=20) who also used a manual wheelchair for daily mobility. Assessment of risk factors: A senior sports physiotherapist and musculoskeletal radiologist obtained measures of SS, PEF, and MSK ultrasound (MSK-U) findings. Relationships between measures and for sub-groups by sporting discipline were calculated. Age, duration of disability, and disability type were evaluated as independent risk factors for pain or structural pathology. Main outcome measurements: The Wheelchair Users Shoulder Pain Index (WUSPI), Physical Examination of the Shoulder Scale (PESS), and the ultrasound Shoulder Pathology Rating Scale (USPRS) Results: A total of 51 of 80 athletes reported dominant shoulder pain. PESS scores were 7.4±6.7, WUSPI 22.3±26.9 and USPRS 5.2±4.0. A positive main effect was found for pain history on PESS (F1, 154=9.57 p=0.002, ηp 2 =0.06) but no interaction with athlete sub-group (F2, 154=1.90 p=0.15, ηp 2 =0.02). There were no USPRS score differences between sub groups, but track athletes had lower WUSPI scores and lower PESS scores. The WUSPI and PESS which were strongly correlated (0.71), while the USPRS which did not correlate with either the PESS (0.21) or WUSPI (0.20). Conclusions: Elite wheelchair athletes have a high prevalence of MSK-U pathology with low-moderate levels of SS and PEF. MSK-U findings do not correlate with SS or PEF. These findings are an important step to educate the development of targeted preventative measures.